Surface Functionality Features of Nanosized Silica Obtained by Electron Beam Evaporation at Ambient Pressure - S. P. Bardakhanov; I. V. Vasiljeva; N. K. Kuksanov; S. V. Mjakin (Advances in Materials Science and Engineering)
A series of nanosized silica powders with different specific surface values are synthesized by electron beam evaporation in air at ambient pressure. The obtained silica samples are featured with relatively low apparent density and high content of oxygen and hydroxyl groups on the surface making these materials promising for specific applications.